Association between advanced lung cancer inflammation index and all-cause mortality in critically ill patients with sepsis: analysis of the MIMIC-IV database - Lei Zhang; Minye Li; Jianfei Liu; Zhanwei Zhao; Lijun Zhou (Scientific Reports)
Abstract This study aimed to explore the association between the advanced lung cancer inflammation (ALI) index and the risk of mortality in critically ill patients with sepsis. This retrospective study included 6489 critically ill patients with sepsis from the Medical Information Mart for Intensive Care-IV (MIMIC-IV) database. The participants were grouped into four groups according to the ALI index quartiles. The outcome was in-hospital mortality and intensive care unit (ICU) mortality. Cox proportional hazards regression analysis and restricted cubic spline regression were used to evaluate the association between the ALI index and clinical outcomes in critically ill patients with sepsis. A total of 6489 patients (59.1% male) were included in the study. The in-hospital and ICU mortality were 25.4% and 19.0%, respectively. Multivariate Cox proportional hazards analysis showed that the ALI index was independently associated with all-cause mortality. After confounders adjusting, ALI index had a significant association with hospital mortality (adjusted hazards ratio, 0.990; 95% confidence interval, 0.985–0.996; P < 0.001) and ICU mortality (adjusted hazards ratio, 0.991; 95% confidence interval, 0.985–0.997; P = 0.004). Restricted cubic splines revealed a non-linear association between ALI and all-cause mortality in sepsis patients. Our study indicates that the ALI index has a significant association with hospital and ICU all-cause mortality in critically ill sepsis patients. However, further confirmation of these findings necessitates larger prospective studies.